Policing & Firearms New Perspectives and Insights - Farmer, Clare; Evans, Richard (Cham : Springer International Publishing : Imprint: Springer, 2023)
Policing and firearms: it is a crucial relationship. Should police be routinely armed? If so, what restrictions should be imposed on the use of firearms? Where police are not routinely armed, there is still a need for specialist armed police: how do these units operate, and are they effective? This ground-breaking edited book explores the nexus between policing and firearms with a genuinely international focus. Contributors from Ireland, Germany, the United Kingdom, Brazil, Mexico, the United States, Venezuela, New Zealand, Australia, and Canada explore the issues from a range of perspectives, including human rights, militarization, police legitimacy, and the risks police firearms pose to the community and to police themselves. This thought-provoking collection is an indispensable resource for law enforcement policymakers and students of policing and criminal justice.
1. Introduction -- Part 1: Policing, Firearms and Human Rights -- 2. Unarmed Police: Myths, Rights and Realities -- 3. Are the Brazilian Police Forces lethal weapons? -- 4. The Routine Arming of the Police in Britain, the Right to Life and the Security Theory of John Locke and Benedict de Spinoza -- 5. Armed responses and Critical Shots: Learning lessons from Police involved shootings in England and Wales -- Part 2: Policing, Firearms and Militarization -- 6. 'Gung-ho'? An examination of the move to militarise policing in Australia -- 7. Direct and indirect militarization of public security in Mexico and gun use during arrests -- 8. The myth of 'routinely unarmed' policing -- 9. Racism down the Barrel of the Colonial Gun -- Part 3: Policing, Firearms and Risk -- 10. Access to firearms - A risk factor for police suicide? -- 11. How do police die in Venezuela? A comprehensive analysis of the death by homicide of State security force/policing officials -- 12. Pathways to preventing fatal police-involved shootings of people in mental health crisis -- 13. 'Facing death gave him new life': On-screen police gun violence and Weapon Product Placement -- Part 4: Policing, Firearms and Legitimacy -- 14. Predictors of public reactions to armed police: Findings from the UK -- 15. Armed police in an unarmed country: Legitimacy and self-legitimacy of English firearms officers -- 16. Public Acceptance of Police Use of Deadly Force: An Exploratory Study -- 17. Connecting officer appearance with officer safety: A survey of police officers' perceptions of uniforms and accoutrements.
Keywords: Criminology; Crime -- Sociological aspects; Public health; Crime Control and Security; Crime and Society; Criminology; Public Health